Ameliorative Effect of Dried Seed Extract of Prunus dulcis (Mill.) D.A. Webb var. amara (DC.) on Scopolamine-induced Memory Impairment in Rats - Shrivastava, Neeraj Kumar; Mukerjee, Alok; Singh, Sunil Kumar; Tripathi, Abhishek Kumar; Srivastava, Arvind Kumar (Indian Journal of Natural Products, 2021)
Present study includes the ameliorating effect of dried extract seed of Prunus dulcis (Mill.) D.A. Webb var. amara (DC.) on Scopolamine hydrobromide (ScHBr) induced memory impairment in rats, cholinesterase activity and oxidative stress. Cognitive disorders include various factors as amnesia, difficulties in attention and Alzheimer’s disease (AD) and other neurologically disorders. Basic mechanism of neuro related disorder underlies with neuroapoptsis. The term Neuroapoptsis means dead of neurons, leads to dementia, abnormal behaviour, psychological changes which may even leads to death of the individuals. Characteristics features of this disease include irregularity in learning and memory, deposition of senile plaques and neurofibrillary tangles, elevated level of Acetylcholinesterase enzyme (AChE) and oxidative stress. Amnesia causing agent includes Scopolamine hydrobromide, which tends to increase AChE activity. Extract dose was administered at 250mg/kg and 500mg/kg of body weight of animals for consecutive 7th and 8th day for Elevated Plus Maze (EPM) and 10th and 11th day for Morris water maze (MWM) to the various groups of animals Standard Nootropic agents was used for this study is Piracetam at a dose of 120mg/kg of body weight. Summary Results indicate that extract of seed have potential to decrease transfer latency at 7th day and 8th day in the EPM task and transfer latency on acquistion day i.e 10th day and transfer latency (TL) on retention day on 11th day in Morris Water Maze. PDWA extract shows decreased the activity of cholinesterase in brain and also exhibited improve antioxidant defence system leads to decrease level of Thiobarbituric acid reactive substance TBARS which is indication of diminished oxidative stress and improve cognitive function.
Keywords: Scopolamine hydrobromide (ScHBr); Prunus dulcis (Mill.); (PDWA); Amnesia; Acetyl cholinesterase (AChE) Thio Barbituric Acid Reactive Substances (TBARS); Cognition